Dimensi Hukum Pengawasan terhadap Penyelenggaraan Otonomi Daerah - Ridwan HR (Fakultas Hukum Universitas Islam Indonesia, 2001)
The regional autonomy should notbe interpreted as theseparation between regional and state authority extremely for the constitution has declared the unity stated clearly to maintain any public interest. In spreading outgoverning powerinto any levelsthe main position to hold the responsibility is laid down upon the govemment. it would be very necessary to classify the provincial rules in order to prevent court system from any distorsion. The government could dismiss any intemal provincial affairs while Supreme Courtcould do so in any public interest or criminal law.